2017
DOI: 10.1515/agri-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Nano and Organic Fertilisers As an Alternative Source to Chemical Fertilisers on Carum Carvi L. Plant Yield and Components

Abstract: Economic evaluation of nano and organic fertilisers as an alternative source to chemical fertilisers on Carum carvi L. plant yield and components. Agriculture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…The increment in number of leaves (Table 4) obtained by zeolite increase photosynthetic surfaces and the current of photosynthetic production of more assimilates which cause a significant increment in the productivity traits. These results in harmony with Polat et al (2004), Gul et al (2005), Ozbahce et al (2014 and Mahmoud et al (2017). Concerning compost effects on fruits quality parameters, this result has the same line with the findings of Santiago et al (2009) and Kashem and Warman (2009).…”
Section: Productivity Attributessupporting
confidence: 89%
“…The increment in number of leaves (Table 4) obtained by zeolite increase photosynthetic surfaces and the current of photosynthetic production of more assimilates which cause a significant increment in the productivity traits. These results in harmony with Polat et al (2004), Gul et al (2005), Ozbahce et al (2014 and Mahmoud et al (2017). Concerning compost effects on fruits quality parameters, this result has the same line with the findings of Santiago et al (2009) and Kashem and Warman (2009).…”
Section: Productivity Attributessupporting
confidence: 89%
“…Nutritional quality significantly influences plant performance, especially in terms of its physiological mechanisms for producing essential oils. Numerous researchers have endorsed these ideas, including Jimayu (2017), Mahmoud et al (2017), Acimovic et al (2015 a & b), Ahmadian et al (2011 and Sangwan (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Subbaiah et al (2016) demonstrated that, nano ZnO increased growth, yield, and Zn content of maize. Still, the agronomic effectiveness of nano practical compared to non-nano forms of micronutrients has yet to be fully resolved (Mahmoud et al 2017).…”
Section: Macro and Micro Nutrients Concentrationsmentioning
confidence: 99%
“…Deficiency of carbohydrates may stimulate the degradation fatty acids to acetyl co-enzyme A and it leads to decreased oil content (Marschner & Rengel 2012). Also, Mahmoud et al (2017) concluded that application of organic fertilisers, natural soil amendments and chemical fertilisers (nano form) produced high er growth characteristics, chemical composition and oil yield in comparison with results derived from chemical fertilisers NPK on caraway plant.…”
Section: Main Sulphur Content Glucose Fructose Ascorbic and Crude mentioning
confidence: 99%